Analysis of the Clinical Efficacy of Laparoscopy and Hysteroscopy in the Treatment of Tubal-Factor Infertility - Nian, Lei; Yang, De-Hong; Zhang, Jie; Zhao, Han; Zhu, Cai-Fen; Dong, Ming-Feng; Ai, Ying (Frontiers in Medicine, 2021)
Objective: This study aimed to investigate the clinical efficacy of laparoscopy and hysteroscopy in the treatment of tubal-factor infertility (TFI) in order to provide a basis for predicting postoperative pregnancy rate. Methods: The clinical data of 336 patients who underwent laparoscopy and hysteroscopy for TFI between February 2018 and December 2018 in the Department of Reproductive Gynecology at the First People’s Hospital of Yunnan were retrospectively analyzed. After imposing the inclusion and exclusion criteria, 278 patients were included in the study. The patients were grouped according to pelvic adhesions, hydrosalpinx, twisted fallopian tubes, and fimbriae structure. The impacts of the extent of fallopian tube diseases on postoperative pregnancy outcome were analyzed. Results: Of the 278 patients, 129 got pregnant (pregnancy rate = 46.4%). Pelvic adhesions, hydrosalpinx, twisted/folded fallopian tubes, and damage to the fimbriae of the fallopian tubes were found to affect natural pregnancy rate after surgery, with the natural pregnancy rate decreasing significantly with the aggravation of the disease (P < 0.001). Of the 129 patients who had natural pregnancies, 29 had ectopic pregnancies (ectopic pregnancy rate = 22.48%). Twisted/folded fallopian tubes and damage to the fimbriae structure significantly increased the incidence of postoperative ectopic pregnancy (P < 0.001). Conclusion: Laparoscopy and hysteroscopy are effective treatments for TFI. Pelvic adhesions, twisted/folded fallopian tubes, hydrosalpinx, and damage to the fimbriae of the fallopian tubes can affect postoperative pregnancy outcomes and lead to a failure of natural pregnancy after operation. The incidence of ectopic pregnancy increases with the degree of fallopian tube twisting/folding and the degree of damage to the fimbriae of the fallopian tubes.